Differential methylation and expression of HUA1 ortholog in three sex types of papaya. (July 2018) - Liu, Juan; Chatham, Laura; Aryal, Rishi; Yu, Qingyi; Ming, Ray
Highlights: CpHUA1 is involved in sex differentiation gene network in papaya. Different sex types display distinct restriction pattern of EcoR I in southern blot. The methylation in CHH context of CpHUA1 is related with temperature stress response and sex reversal in papaya. Abstract: Papaya is trioecious and an excellent system for studying sex determination and differentiation in plants. An ortholog of HUA1, CpHUA1, a gene controlling stamen and carpel development in Arabidopsis, was cloned and characterized in papaya . CpHUA1 consists of 12 exons with full genomic length of 19, 313 bp in male AU9 and 19, 312 bp in hermaphrodite SunUp, whereas the Arabidopsis HUA1 consists of 12 exons with full genomic length of 4300 bp. All the 324 SNPs between male and hermaphrodite varieties are in the 11th intron, which spans 8.5 kb. Quantitative RT-PCR revealed that CpHUA1 expression is highly elevated in carpels, suggesting that CpHUA1 may be involved in sex differentiation gene network. Southern blot analysis revealed a distinct restriction pattern in male AU9 compared to hermaphrodite Kapoho and SunUp, despite high DNA sequence identity and sharing of all but two Eco R I restriction sites in genomic CpHUA1 sequences of AU9 and SunUp. The methylation of cytosine at one restriction site in male but not in other two sex types may result in distinct restriction pattern of Eco R I in southern blot result. Bisulfite sequencing showed differential methylation of CpHUA1 among sex types, particularly the enrichment of sex-specific methylation in 9th and 11th intron. The methylation difference in cold stress induced male to hermaphrodite mutant mostly observed in the CHH context of CpHUA1, but no methylation difference detected in CHH context in other sex types, which may indicate the role of methylation in CHH context of CpHUA1 in temperature-related stress response and sex reversal.